INOVASI PESANTREN DALAM MEMBENTUK KEMANDIRIAN LEMBAGA DAN SANTRI - Siti Nurjanah; M. Kholis Amrullah (Postgraduate State Islamic Institute (IAIN) Metro, 2021)
Pesantren as a place to gain religious knowledge that is simple and does notcharge a lot of money. In facing the times, pesantren are required to beindependent, and santri are also required to be independent when they enter thecommunity. This study aims to reveal the innovations of pesantren in establishingindependence through the results of several studies related to pesantren activitiesin developing and improving the quality of pesantren and their students. Theresults of this study indicate that pesantren provide students with religiousknowledge, entrepreneurship skills, and social skills to prepare students to enterreal life.